Penerapan Asimilasi Di Lembaga Pemasyarakatan Pada Masa Covid-19 - Syarunsyah Syarunsyah; Suriani Suriani; Novita Sinaga (Universitas Semarang, 2023)
The purpose of the study was to examine the regulation of the application of assimilation during the Covid-19 period in prisons in order to reduce the level of spread of Covid-19 in prisons. The Indonesian government through the Ministry of Law and Human Rights adopted a policy of releasing convicts to break the chain of Covid-19. This research is important to do to find out the policy for the release of prisoners in terms of breaking the Covid-19 chain which in this case is the authority of the Indonesian Government through the Ministry of Law and Human Rights. This study uses empirical legal research methods that contain data in the field directly at the Class II B Correctional Institution Tanjungbalai Asahan. This research has a focus of study, namely providing assimilation during the Covid-19 period. Government policies through the Ministry of Law and Human Rights in implementing assimilation in Correctional Institutions during Covid-19 and the effect of implementing assimilation on crime rates. Based on the results of this study, it is known that the release is carried out through an assimilation and integration process in the form of parole, leave before release, and prisoners whose 2/3 of their sentences fall from April 1, 2020 to December 31, 2020. The release of adult and child prisoners to break the chain the spread of Covid-19 The Tanjungbalai Asahan District Prosecutor's Office has provided assimilation of 36 (thirty-six) inmates from the Class II B Penitentiary of Tanjungbalai Asahan. Providing assimilation does not have a significant impact on crime rates. Tujuan penelitian untuk menganalisis regulasi penerapan asimilasi pada masa Covid-19 di lembaga pemasyarakatan guna mengurangi tingkat penyebaran Covid-19 di lembaga pemasyarakatan. Pemerintah Indonesia melalui Kementerian Hukum dan HAM mengambil kebijakan pembebasan narapidana untuk memutus mata rantai Covid-19. Penelitian ini penting dilakukan untuk mengetahui kebijakan pembebasan narapidana dalam hal untuk memutus mata rantai Covid-19 yang dalam hal ini merupakan wewenang Pemerintah Indonesia melalui Kementrian Hukum dan HAM. Penelitian ini mengunakan metode penelitian hukum empiris yang memuat data dilapangan secara langsung di Lembaga Permasyarakatan Kelas II B Tanjungbalai Asahan. Penelitian ini memiliki fokus kajian yaitu pemberian asimilisasi pada masa Covid-19. Kebijakan Pemerintah melalui Kementerian Hukum dan HAM dalam menerapkan asmilisasi di Lembaga Permasyarakatan pada Covid-19 dan pengaruh penerapan asimilasi terhadap tingkat kejahatan. Berdasarkan hasil penelitian ini diketahui bahwa pembebasan dilakukan melalui proses asimilasi dan integrasi berupa pembebasan cuti bersyarat, cuti menjelang bebas, dan narapidana yang 2/3 masa hukumannya jatuh pada tanggal 1 April 2020 hingga 31 Desember 2020. Pembebasan narapidana dewasa dan anak untuk memutus mata rantai penyebaran Covid-19. Pembebasan dilakukan melalui proses asimilasi dan integrasi berupa pembebasan cuti bersyarat, cuti menjelang bebas, dan narapidana yang 2/3 masa hukumannya jatuh pada tanggal 1 April 2020 hingga 31 Desember 2020. Pembebasan narapidana dewasa dan anak untuk memutus mata rantai penyebaran.Pemberian asimilasi tidak memberikan dampak yang signifikan terhadap tingkat kejahatan.